Marriage Dispensation in Indonesia on The Perspective of Maqāṣid Al-Usrah - Sanuri, Sanuri (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2021)
Currently, the number of early marriage or underage marriage in Indonesia has increased sharply. In 2020, there are approximately 34,000 applications for marriage dispensation to the courts.. Of that number, 97% of the requests were granted. This means that almost all applicants for marriage dispensation are granted by the courts. Therefore, to measure whether the dispensation of the underage marriage has met the standart of maslahah for the perpetrator or not, it will be analyzed using the theory of maqāṣid al-usrah. The results of the research state that: (1) the motives for conducting underage marriage are due to economic factor, government policy to close schools during the Covid-19 pandemic, the rise of glorification of marriage on social media, and incidents of pregnancy out of wedlock; (2) giving dispensation by the courts to the applicants to continue conducting underage marriage is legally valid as fiqh al-munākaḥāt fiqh (Isalmic jurisprudence on marriage), but it can turn into ḥarām if the potential of harm is greater than the benefit for the bride and groom. [Saat ini, angka pernikahan dini atau pernikahan di bawah umur di Indonesia mengalami peningkatan tajam. Di tahun 2020, ada sekitar 34.000 permohonan dispensasi kepada pengadilan. Dari jumlah itu sebanyak 97% permohonan dikabulkan. Ini artinya hampir semua pemohon dispensasi nikah dikabulkan oleh pengadilan. Oleh sebab itu, untuk menakar apakah dispensasi pernikahan di bawah umur sudah memenuhi standar maslahah bagi pelaku atau belum, maka akan dianalisis menggunakan teori maqa>sid al-usrah. Hasil penelitian menyebutkan bahwa: (1) motifasi melangsungkan pernikahan di bawah umur adalah karena faktor ekonomi; Kebijakan pemerintah untuk melakukan penutupan sekolah selama masa pandemic covid-19; maraknya glorifikasi perkawinan di media social; dan terjadinya insiden hamil di luar nikah; (2) pemberian dispensasi oleh pengadilan kepada para pemohon untuk tetap melangsungkan pernikahan di bawah umur adalah sah secara hukum fikih munakahat, akan tetapi bisa berubah menjadi haram jika potensi bahayanya lebih besar dari manfaatnya bagi mempelai berdua.]